Weather regimes in the South American sector and neighbouring oceans during winter - Solman, Silvina Alicia; Menendez, Claudio Guillermo (Climate Dynamics)
We classified 34 years of winter daily 500 hPa geopotential height patterns over the eastern South Pacific-South America-South Atlantic region using the K-means clustering method. We found a significant classification into five weather regimes (WRs) defined as the most frequent large-scale circulation anomalies: WR1 (trough centred downstream of the Drake Passage), WR2 (trough over the SW Pacific and ridge downstream), WR3 (ridge over the SE Pacific and NW–SE trough downstream), WR4 (trough over the SE Pacific and NW–SE ridge downstream) and WR5 (weak ridge to the west of southern South America). We also analysed their persistence and temporal evolution, including transitions between them and development around onsets and breaks of each regime. The preferred transitions, WR1→WR3→WR2→WR4→WR1 and also WR1→WR3→WR2→WR1, suggest the progression of a Rossby wave-like pattern in which each of the regimes resemble the Pacific-South America modes. Significant influence of the WRs on local climate over Argentina was found. The preferred transitions WR1→WR3 and WR3→WR2 induce sustained cold conditions over Patagonia and over northern Argentina, respectively. The most significant change in precipitation frequency is found for WR3, with wetter conditions over all the analysed regions. Finally, the interannual to interdecadal significant variations in the occurrence of these regimes were discussed. WR1 and WR3 are more frequent and WR2 is less frequent during El Niño, and WR2 and WR5 are more frequent and WR1 is less frequent during La Niña. A significant decrease in WR2 and increase of WR4 and WR5 during the 1970s and early 1980s were found. Fil: Solman, Silvina Alicia. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Centro de Investigaciones del Mar y la Atmósfera. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Centro de Investigaciones del Mar y la Atmósfera; Argentina Fil: Menendez, Claudio Guillermo. Consejo Nacional de ...